Effects of Polygamous Families on Children in Mukunyu Sub County Kasese District - Biira, Juliet (Mukono : Uganda Christian University, 2009)
Discriptive Cataloguing Uganda Christian University BCDCM
Includes Appendix and References
Keywords: Children -- Poligamy